Development of process safety management system (PSMS): Mechanical integrity (MI) - Aziz, H.A. (Trans Tech Publications Ltd, 2014)
Accident is one of the big issues that occur repeatedly in the process industries today though there is numerous application of the variety safeguarding measures that have been introduced. Equipment failure is identified as one of the root causes of these major accidents. One of the established standards that addressed the above issue is a Mechanical Integrity (MI) element of Process safety Management System (PSM) 29 CFR 1910.119(j). The main objective of this study is to introduce a systematic technique to implement PSM MI in process industries. This study covered analysis of requirements of the standard, development of framework and prototype tool as well as concept validation through a case study. Implementation of this technique will help employers to prevent major accidents and compliance to the PSM standard simultaneously. Â© 2014 Trans Tech Publications, Switzerland.